2022
DOI: 10.3390/ijerph192013242
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Spirituality, Religious Fundamentalism and Environmentalism: The Mediating Role of Right-Wing Authoritarianism

Abstract: According to past research, religious attitudes can strongly influence individuals’ beliefs and behaviors. The purpose of this study was to assess the relationships between spirituality (the Scale of Spirituality; dimensions include religious spirituality, expanding consciousness, searching for meaning, sensitivity to art, doing good, and sensitivity to inner beauty), religious fundamentalism (the Religious Fundamentalism Scale), support for right-wing authoritarianism (the Right-Wing Authoritarianism Scale), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Numerous studies have also ascertained that spirituality reduces stress, thereby contributing to reduced cardiovascular reactivity, hypothalamic–pituitary–adrenal axis activation, and inflammation, which may consequently improve health outcomes [ 64 ]. In the case of ecological behaviour, Skalski et al [ 15 ] noted that spirituality encourages the promotion of ecology through central educational and pro-social values. In the adaptation study, we also showed negative mean associations of spirituality with PTSD symptom severity and depressive symptoms, which also demonstrates the accuracy of the convergent Polish version of the IFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have also ascertained that spirituality reduces stress, thereby contributing to reduced cardiovascular reactivity, hypothalamic–pituitary–adrenal axis activation, and inflammation, which may consequently improve health outcomes [ 64 ]. In the case of ecological behaviour, Skalski et al [ 15 ] noted that spirituality encourages the promotion of ecology through central educational and pro-social values. In the adaptation study, we also showed negative mean associations of spirituality with PTSD symptom severity and depressive symptoms, which also demonstrates the accuracy of the convergent Polish version of the IFS.…”
Section: Discussionmentioning
confidence: 99%
“…The tool includes 16 statements arranged into a single factor (α = 0.79) that identify behaviours related to recycling, energy and water conservation, shopping, and moving around. In the Polish version [ 15 ], the participant expresses their attitude toward each statement on a five-point Likert scale, where 1 = “ Definitely not ” and 5 = “ Definitely yes ”. Sample items include: “ Buying seasonal fruits/regional vegetables” and “ No car in household”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the perception of wondering awe is much higher in people with a spiritual/religious background and thus more frequent practices that may sensitize these individuals for these perceptions ( 38 , 59 ). According to Skalski, et al ( 70 ), spirituality reflects a personal relationship with the divine and thus positively predicts a sense of connection with nature. On the other hand, the literature on the relationship between religion and nature has been inconclusive ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the literature on the relationship between religion and nature has been inconclusive ( 71 ). Recent findings, however, indicate that religion can foster perceptions of nature, and any negative relationship between these variables is fully explained by religious fundamentalism and support for authoritarianism ( 70 ). We should also note that Pope Francis, as the leader of the Catholic Church, has pointed out in one of his encyclicals that it is necessary to combine concern for the environment with a sincere love of humanity and with an ongoing commitment to society's problems ( 72 ).…”
Section: Discussionmentioning
confidence: 99%